The changing epidemiology of Clostridioides difficile infection and the NAP1/027 strain in two Québec hospitals: a 17-year time-series study - Sandrine Couture; Charles Frenette; Ian Schiller; Rowin Alfaro; Nandini Dendukuri; Daniel Thirion; Yves Longtin; Vivian G. Loo (Antimicrobial Stewardship & Healthcare Epidemiology, 2024)
Abstract